INFORMATIONAL ASSESSMENT OF A SELECTED SET OF DIAGNOSTIC INDICATORS OF A CONTROLLED OBJECT - KUTIN, VASYL; KUTINA, MARYNA; KOVALOV, ARTEM (Herald of Khmelnytskyi National University. Technical sciences, 2025)
A study of changes in the technical condition of electrical installations during operation has been conducted. It has been shown that it is possible to distinguish such a set of indicators (parameters of the technical condition of structural elements or diagnostic) that can change during operation and significantly affect the operability of the object. To detect damage at an early stage of its development, methods and means are used that provide a high level of sensitivity to changes in the technical condition of the element (object of diagnosis). For complex systems, the cost of such means may exceed the economic effect of diagnostics, therefore studies are being conducted to reduce the number of controlled indicators. In addition, a large number of indicators leads to the processing of significant amounts of information, which is not always justified. The paper proposes a methodology for determining the impact of changes in the technical condition of each parameter on the operability of the object and an informational assessment of the selected set of indicators.  It is shown that by assessing the amount of information carried by each indicator, it is possible to determine the probability of a correct assessment of the actual technical condition of the object, which can be obtained when performing the selected inspection. Determining the probability requires taking into account two factors: the weighting characteristic of each indicator and the technical characteristic of the object. Knowing the probability of a correct assessment of the actual condition of the object, it is possible to determine the degree of uncertainty of the object's condition, which remains when controlling a limited number of indicators. It is also possible to determine the information about the actual condition of the object, which we will obtain when performing an inspection or a set of inspections, and calculate it. The paper considers an example of information assessment.
Keywords: technical condition; damage; correct assessment of the condition of the object